Respostas

2013-11-18T11:35:48-02:00
L )
3x-6+8x=4+12x-6
3x+8x-12x=4-6+6
11x-12x=4
-x=4
x=-4

M )
x+105+x=24-x+36
2x+x=24+36-105
3x=50-105
3x=-55
x=-55/3

N )
 3x+36+2x=18-x+12
3x+2x+x=18+12-36
4x=-6
x=-6/4
x=-3/2

O )
2x-66+2x=30-2x-144
2x+2x+2x=30-144+66
6x=-48
x=-48/6
x=-8

P )
x-33+x=15-x-72
x-x+x=15-72+33
x=-24

Q )
4x+28-x=35-3x+49
4x-x+3x=35+49-28
6x=56
x=56/6
x=28/3

R )
2x+14-x=18-3x+24

2x-x+3x=18+24-14
4x=28
x=28/4
x=7

S)
3x-18-x=12+4x-40
3x-x-4x=12-40+18
-2x=-10
2x=10
x=10/2
x=5

T )
25-2x+18=-2x+15-2x
-2x+2x+2x=15-18
2x=-3
x=-3/2


1 5 1